ISPyB for BioSAXS, the gateway to user autonomy in solution scattering experiments. (1st January 2015) - De Maria Antolinos, Alejandro; Pernot, Petra; Brennich, Martha E.; Kieffer, Jérôme; Bowler, Matthew W.; Delageniere, Solange; Ohlsson, Staffan; Malbet Monaco, Stephanie; Ashton, Alun; Franke, Daniel; Svergun, Dmitri; McSweeney, Sean; et al.
<x xml:space="preserve">Abstract</x> Logging experiments with the laboratory‐information management system ISPyB (Information System for Protein crystallography Beamlines) enhances the automation of small‐angle X‐ray scattering of biological macromolecules in solution (BioSAXS) experiments. The ISPyB interface provides immediate user‐oriented online feedback and enables data cross‐checking and downstream analysis. To optimize data quality and completeness, ISPyBB (ISPyB for BioSAXS) makes it simple for users to compare the results from new measurements with previous acquisitions from the same day or earlier experiments in order to maximize the ability to collect all data required in a single synchrotron visit. The graphical user interface (GUI) of ISPyBB has been designed to guide users in the preparation of an experiment. The input of sample information and the ability to outline the experimental aims in advance provides feedback on the number of measurements required, calculation of expected sample volumes and time needed to collect the data: all of this information aids the users to better prepare for their trip to the synchrotron. A prototype version of the ISPyBB database is now available at the European Synchrotron Radiation Facility (ESRF) beamline BM29 and is already greatly appreciated by academic users and industrial clients. It will soon be available at the PETRA III beamline P12 and the Diamond Light Source beamlines I22 and B21.